PROGRAM LATIHAN PEREGANGAN DAN LATIHAN BEBAN UNTUK CABANG OLAHRAGA RENANG - Alpina Damayanti Siregar; Khairul Akbar Sihaloho; Shafwan Shabir; Habib Rizki Purba; Nurhayati Simatupang (STKIP Subang, 2026)
Swimming is a sport that demands an optimal synergy between articular flexibility, prime mover muscle strength, and biomechanical efficiency. However, many junior training programs still rely heavily on aquatic training volume without systematic integration of dry-land components. This study aims to analyze the effect of a dynamic-static stretching program combined with periodized resistance training on increasing flexibility, muscle strength, and 50-meter freestyle swim time in junior swimmers. A quasi-experimental design with a pre-test and post-test control group design was used. The sample consisted of 40 swimmers aged 15–17 years selected through purposive sampling and randomly divided into an experimental group (n=20) and a control group (n=20). The experimental group underwent an 8-week intervention, 3 sessions/week, including pre-training dynamic stretching, post-training static stretching, and progressive resistance training (60–85% 1RM) focused on the latissimus dorsi, rotator cuff, core stabilizers, and hip flexors-extensors. The control group continued their routine aquatic training program without a structured stretching/resistance training component. Data collection instruments included a sit-and-reach box, an isokinetic dynamometer, and an electronic timing system for the 50m freestyle test. Data analysis used ANCOVA with the pre-test as a covariate, at a significance level of α = 0.05. The results showed a significant increase in the experimental group compared to the control group for flexibility (p = 0.003; d = 1.12), shoulder muscle peak torque (p < 0.001; d = 1.45), and 50m freestyle swim time (p = 0.012; d = 0.89). The discussion confirms that periodic integration of stretching and resistance training can reduce connective tissue stiffness, increase motor unit recruitment, and improve stroke length and efficiency. This program is recommended as a mandatory component in junior swimming athlete development to maximize physiological adaptation and minimize the risk of overuse injuries.